2016
DOI: 10.1002/gps.4552
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with daily challenges in dementia (deal‐id study): an experience sampling study to assess caregiver functioning in the flow of daily life

Abstract: The ESM is a feasible method to assess caregiver functioning. In addition to standard retrospective measurements, it offers new opportunities to gain more insight into the daily lives of people with dementia and their caregivers. It also provides new possibilities to tailor caregiver support interventions to the specific needs of the caregiver. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…To our knowledge, no other study has reported process evaluation outcomes of an ESM intervention for caregivers of people with dementia. The application of ESM in the field of dementia is still in its infancy (van Knippenberg et al, 2016c). Our study, therefore, provides valuable information for future implementation of ESM as a supportive tool in clinical practice.…”
Section: Strengths and Weaknessesmentioning
confidence: 88%
See 2 more Smart Citations
“…To our knowledge, no other study has reported process evaluation outcomes of an ESM intervention for caregivers of people with dementia. The application of ESM in the field of dementia is still in its infancy (van Knippenberg et al, 2016c). Our study, therefore, provides valuable information for future implementation of ESM as a supportive tool in clinical practice.…”
Section: Strengths and Weaknessesmentioning
confidence: 88%
“…The feasibility of the 'PsyMate' in caregivers of PwD has recently been demonstrated (van Knippenberg et al, 2016c). During the six-week intervention period, the 'PsyMate' was programmed to generate 10 alerts (sound and vibration) per day for three consecutive days per week (6 £ 10 £ 3 = 180 beeps in total).…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, participants received an electronic ESM device, the ‘PsyMate’ [ 31 ], to collect data in their daily lives. The feasibility of the ‘PsyMate’ in caregivers of PwD has recently been demonstrated [ 32 ]. A 30-minute training session was provided to explain the ESM procedure and how to operate the ‘PsyMate’.…”
Section: Methodsmentioning
confidence: 99%
“…Actors outside of the workplace of the managers and staff such as general practitioners, occupational therapists, and registered nurses specialized in dementia care, are important resources as dementia progresses over time, but other means may also be considered. Research showing promising results using a digital diary method such as the Experience Sampling Method (ESM), which was described by Knippenberg et al [ 34 ] to assess caregiver functioning, has emerged. The method is mainly designed for spousal caregivers to persons with dementia, but, since the relationship between professional caregivers and individuals with IDs and dementia is often long-term, it should be possible to develop similar digital methods that are refined and adapted to this caring relationship.…”
Section: Discussionmentioning
confidence: 99%